Assessing the efficacy of nitrogen isotopes to distinguish Colorado Front Range ammonia sources affecting Rocky Mountain National Park. (15th October 2019) - Stratton, J.J.; Ham, Jay; Collett, Jeffrey L.; Benedict, Katie; Borch, Thomas
1. Abstract: Rocky Mountain National Park (RMNP) is experiencing negative ecosystem impacts due to nitrogen (N) deposition, which occurs in the forms of ammonium, nitrate and organic N. In order to complement other source apportionment approaches, the efficacy of N isotopes of ammonia to distinguish sources of ammonia deposited in RMNP was investigated. This study reports ammonia concentrations and demonstrates that the average δ 15 N–NH3 isotopic ratios of certain sources (beef cattle production, −20.9‰; dairies, −28.2‰; wastewater treatment plants, −35.7‰, cropland −26.4‰, urban −16.9‰) were distinguishable (p < 0.05) based on measurements at the emission sites; but, the average δ 15 N–NH3 (−29.9‰) measured at the receptor site in RMNP could not be used for direct ammonia source apportionment. Weekly integrations of gaseous and particulate N and sulfur measurements, and of N and sulfur in wet deposition measurements were used to explore how transport and secondary reactions may have affected the δ 15 N ratios observed in wet deposition. Post emission physical and chemical processes, such as isotopic fractionation likely influenced the δ 15 N–NH3 to such a degree that measurements in RMNP were no longer representative of the isotope signatures from their original sources. These results highlight the need to better understand isotope fractionation between gaseous and aerosol phases. Graphical abstract: Image 1 Highlights: Ammonia concentrations strongly dependent on source type and temperature. Nitrogen isotopic values of ammonia at some emissions sources were distinguishable. Understanding changes during transport recommended for tracing isotopes for ammonia.